Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

For which pair of functions is [tex][tex]$(f \circ g)(x) = x$[/tex][/tex]?

A. [tex]f(x) = x^2[/tex] and [tex]g(x) = \frac{1}{x}[/tex]
B. [tex]f(x) = \frac{2}{x}[/tex] and [tex]g(x) = \frac{2}{x}[/tex]
C. [tex]f(x) = \frac{x-2}{3}[/tex] and [tex]g(x) = 2 - 3x[/tex]
D. [tex]f(x) = \frac{1}{2} x - 2[/tex] and [tex]g(x) = \frac{1}{2} x + 2[/tex]


Sagot :

To determine which pair of functions satisfies the condition [tex]\((f \circ g)(x) = x\)[/tex], we need to compute the compositions [tex]\(f(g(x))\)[/tex] for each pair and check if they simplify to [tex]\(x\)[/tex].

### Pair 1: [tex]\(f(x) = x^2\)[/tex] and [tex]\(g(x) = \frac{1}{x}\)[/tex]
Compute [tex]\(f(g(x))\)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{x}\right) = \left(\frac{1}{x}\right)^2 = \frac{1}{x^2} \][/tex]
For [tex]\((f \circ g)(x) = x\)[/tex] to hold:
[tex]\[ \frac{1}{x^2} = x \][/tex]
This equation is not true for all [tex]\(x\)[/tex].

### Pair 2: [tex]\(f(x) = \frac{2}{x}\)[/tex] and [tex]\(g(x) = \frac{2}{x}\)[/tex]
Compute [tex]\(f(g(x))\)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{2}{x}\right) = \frac{2}{\frac{2}{x}} = \frac{2 \cdot x}{2} = x \][/tex]
In this case, [tex]\((f \circ g)(x) = x\)[/tex] holds.

### Pair 3: [tex]\(f(x) = \frac{x-2}{3}\)[/tex] and [tex]\(g(x) = 2 - 3x\)[/tex]
Compute [tex]\(f(g(x))\)[/tex]:
[tex]\[ f(g(x)) = f(2 - 3x) = \frac{(2 - 3x) - 2}{3} = \frac{2 - 3x - 2}{3} = \frac{-3x}{3} = -x \][/tex]
For [tex]\((f \circ g)(x) = x\)[/tex]:
[tex]\[ -x = x \][/tex]
This is not true for all [tex]\(x\)[/tex].

### Pair 4: [tex]\(f(x) = \frac{1}{2}x - 2\)[/tex] and [tex]\(g(x) = \frac{1}{2}x + 2\)[/tex]
Compute [tex]\(f(g(x))\)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{2}x + 2\right) = \frac{1}{2}\left(\frac{1}{2}x + 2\right) - 2 = \frac{1}{4}x + 1 - 2 = \frac{1}{4}x - 1 \][/tex]
For [tex]\((f \circ g)(x) = x\)[/tex]:
[tex]\[ \frac{1}{4}x - 1 = x \][/tex]
This is not true for all [tex]\(x\)[/tex].

Given the above computations, the pair of functions that satisfies [tex]\((f \circ g)(x) = x\)[/tex] is:

[tex]\[ f(x) = \frac{2}{x} \quad \text{and} \quad g(x) = \frac{2}{x} \][/tex]

Thus, the correct pair is the second pair.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.